Levels of Some Heavy Metals in Raw Cow's Milk from Selected Milk Production Sites in Iran: Is There any Health Concern? - Mohamadreza Arianejad; Mohammad Alizadeh; Arash Bahrami; Seyed Rafie Arefhoseini (Tabriz University of Medical Sciences, 2015)
Background: The aim of this study was to evaluate the content of mercury (Hg), arsenic (As), nickel (Ni) and tin (Sn) in raw cow's milk of traditional and industrial sites from 8 different sites in Arak City, Markazi Province, Iran. Methods: In this cross sectional study, a total of 32 samples were collected from sub-cities of Arak, Iran via subjective sampling method. Both industrial and traditional dairy farms were selected for sampling. Twenty-five gram of each sample was turned to ash in ovens for metal analyses including Hg, As, Ni and Sn by anatomic absorption spectrometer. Results: The residue amounts of Hg and As were lower than permissible limit suggested by Codex Alimentarius, but for Ni and Sn it was higher only in one of the collection sites. The average concentration of Hg was significantly higher (P<0.05) in traditional farms as compared to industrial farms. Besides, amounts of Sn was significantly high in the traditional farms (P<0.05). Further, a high contents Ni was detected in industrial farms (P<0.05). Conclusion: High Sn and Ni contents of some milk samples from this region might be potentially hazardous to consumers. Further, none of the other metals tested crossed permissible levels.